Commissioning of a high pressure time projection chamber with optical readout - Deisting,A; Waldron,A; Atkin,E; Barker,G; Basharina-Freshville,A; Betancourt,C; Boyd,S; Brailsford,D; Chen-Wishart,Z; Cremonesi,L; Dias,A; Dunne,P; et al. (Instruments, 2021)
The measurements of proton–nucleus scattering and high resolution neutrino–nucleus interaction imaging are key in reducing neutrino oscillation systematic uncertainties in future experiments. A High Pressure Time Projection Chamber (HPTPC) prototype has been constructed and operated at the Royal Holloway University of London and CERN as a first step in the development of a HPTPC that is capable of performing these measurements as part of a future long-baseline neutrino oscillation experiment, such as the Deep Underground Neutrino Experiment. In this paper, we describe the design and operation of the prototype HPTPC with an argon based gas mixture. We report on the successful hybrid charge and optical readout using four CCD cameras of signals from 241Am sources.